The crosstalk between SND1 and PDCD4 is associated with chemoresistance of non-small cell lung carcinoma cells - Yun Zhao; Shanel Dhani; Vladimir Gogvadze; Boris Zhivotovsky (Cell Death Discovery)
Abstract Lung cancer is the leading cause of cancer-related deaths worldwide. Non-small cell lung cancer (NSCLC) is highly resistant to chemo- or radiation therapy, which poses a huge challenge for treatment of advanced NSCLC. Previously, we demonstrated the oncogenic role of Tudor Staphylococcal nuclease (TSN, also known as Staphylococcal nuclease domain-containing protein 1, SND1), in regulating chemoresistance in NSCLC cells. Here, we showed that silencing of SND1 augmented the sensitivity of NSCLC cells to different chemotherapeutic drugs. Additionally, the expression of PDCD4 (a tumor suppressor highly associated with lung cancer) in NSCLC cells with low endogenous levels was attenuated by SND1 silencing, implying that SND1 might function as a molecular regulator upstream of PDCD4. PDCD4 is differentially expressed in various NSCLC cells. In the NSCLC cells (A549 and H23 cells) with low expression of PDCD4, despite the downregulation of PDCD4, silencing of SND1 still led to sensitization of NSCLC cells to treatment with different chemotherapeutic agents by the inhibition of autophagic activity. Thus, a novel correlation interlinking SND1 and PDCD4 in the regulation of NSCLC cells concerning chemotherapy was revealed, which contributes to understanding the mechanisms of chemoresistance in NSCLC.